Novel, Reproducible, Consortia Factors Derived from Adipose Stem Cells for Burn Wound Treatment - Talavera-Adame D; Palomares M; Plaza MR; Rogowski N; Lee BS; Zemach A; Newman N (Stem Cells and Cloning: Advances and Applications)
Dodanim Talavera-Adame,1,2 Melissa Palomares,1 Mikhail R Plaza,1 Nualla Rogowski,2 Bong Seop Lee,1 Assaf Zemach,1 Nathan Newman1,2 1Research Facility, Rinati Skin, LLC, Hawthorne, CA, 90250, USA; 2Head Office, Rinati Skin, LLC, Beverley Hills, CA, 90210, USACorrespondence: Nathan Newman, Research Facility and Head Office, Rinati Skin, LLC, Beverly Hills, CA, 90210, USA, Tel +1 (310) 273-3344, Email Dr.Newman@Rinatiskin.comIntroduction: The therapeutic application of adipose-derived stem cells (ASCs) for wound healing has been reported. However, consistently controlling ASC secretory-factor levels, scaling up, and their mechanism of action have been poorly understood, which are critical steps for developing biological drugs to treat second-degree burns.Objective: Our goal is to develop a biological product, named consortia factors-δ 2 (CFx-δ 2), derived from cell-to-cell interactions between human immortalized ASCs using our patented technology and to evaluate the product consistency and in vitro biological effects to enhance the wound healing process.Methods: To assess product consistency, three batches of CFx-δ 2 were analyzed and compared using immunomicroarray and metabolomics. The biological effects of these batches were studied using an in vitro wound healing assay and ex vivo human skin explants subjected to burn wounds. Anti-inflammatory effects were analyzed by inhibition of Nuclear Factor- κB (NF-κB) nuclear translocation in human dermal endothelial cells (HMEC-1). Finally, pro-angiogenesis was evaluated by the induction of tube-like structures and capillary networks in HMEC-1 cells promoted by CFx-δ 2.Results: Our technology enabled the production of CFx-δ 2 with enhanced efficiency and quality. When the three batches were compared, we found high consistency in the pattern and levels of cytokines as well as a strong correlation in the metabolite pattern. Accelerated wound healing was observed after in vitro and ex vivo wound treatment with CFx-δ 2 in comparison to controls. The nuclear translocation of NF-κB, induced by Lipopolysaccharides (LPS), was 50% inhibited by CFx-δ 2. Induction of more tube-like structures and networks was observed in endothelial cells treated with CFx-δ 2 in comparison to controls.Discussion: These findings demonstrate that our technology is efficient to derive and scale up consistent levels of CFx-δ 2 from immortalized adipose stem cells. The product accelerates wound healing by increasing fibroblast proliferation and migration, inhibiting inflammation, and promoting angiogenesis.Keywords: wound healing, burn treatment, stem cells